The relationship between gratitude and psychological wellbeing in adult women : The mediating role of meaning of life - Sri Wahyuni; Mutiara Meidyta (Insight: Jurnal Ilmiah Psikologi, 2024)
Psychological wellbeing is crucial for adults, as it impacts their mental and physical health, social relationships, work, personal growth, resilience, and overall life satisfaction. The objective of this study is to thoroughly examine the correlation between gratitude and its dimensions with the psychological wellbeing of adult women, with meaning of life as a mediator. Participants in this study were 270 middle-aged women aged between 40-60 years, Muslim, and domiciled in Padang Terubuk Village, Senapelan Sub-district, Pekanbaru City, Riau Province using incidental sampling technique. The measurement instruments used were the psychological wellbeing scale, gratitude scale, and meaning of life scale. The data analysis technique used was mediation regression analysis using bootstrapping of the PROCESS macro-Hayes. The research results indicate that gratitude can positively contribute to psychological wellbeing, both directly and when mediated by meaning of life. The contribution of gratitude to psychological wellbeing is greater when mediated by meaning of life compared to when correlated directly. This implies that when individuals express gratitude for their lives, their lives become more meaningful, ultimately resulting in psychological wellbeing. Keyword: Gratitude; meaning of life; psychological well-being.